Zoning of Mucosal Phenotype, Dysplasia, and Telomerase Activity Measured by Telomerase Repeat Assay Protocol in Barrett's Esophagus - Going, James J (Neoplasia Press Inc., 2004)
Glandular dysplasia in Barrett's esophagus may regress spontaneously but can also progress to cancer. The human telomerase RNA template and the human telomerase reverse transcriptase enzyme which do not, of themselves, correlate strongly with telomerase activity, are too often overexpressed in Barrett's dysplasia to predict individual cancer risk. This study relates telomerase activity, mucosal phenotype, and dysplasia in Barrett's esophagus. Biopsies (n = 256) from squamous esophagus, columnar-lined esophagus every 2 cm, esophago-gastric junction, gastric body, and antrum from 32 patients with long-segment Barrett's esophagus were evaluated by telomerase repeat assay protocol (TRAP). Three biopsies for histology (n = 794) were simultaneously taken at each anatomical level. These and all prior and subsequent biopsies (n = 1917) were reviewed for mucosal phenotypes and dysplasia severity. Intestinal-type Barrett's mucosa was present at all levels in Barrett's esophagus. At least one Barrett's biopsy was TRAP(+) in 22 of 32 patients. TRAP positivity of intestinal-type Barrett's mucosa increased distally, possibly as a consequence of mucosal exposure to acid or bile reflux. Native gastric mucosa was rarely TRAP(+) (1/31 corpus, 2/32 antrum), whereas native squamous mucosa usually was TRAP(+) (31/32). Dysplasia almost always involved intestinal-type Barrett's mucosa (85/87; P < .00001), without evidence of proximal-distal zoning. TRAP could be positive without dysplasia and negative in extensive, even high-grade, dysplasia. TRAP activity merits evaluation as a candidate biomarker for increased risk of persistent dysplasia and cancer progression in Barrett's esophagus.